(untitled) (Research, Society and Development, 2025)
Preemergence herbicides (PRE) control weeds at early growth stages and provide a competitive advantage for crop plants during the period of residual action in soil. However, the residual activity of a herbicide can last long enough to cause injury to plants grown in succession, an effect known as carryover. Therefore, the objective of this study was to estimate the residual activity period of the herbicides diuron, indaziflam, metribuzin, and sulfentrazone applied in PRE to a Oxisol with a sandy clay loam texture through bioassays. Each herbicide represented a separate experiment, installed in pots in an open-air nursery in a completely randomized design with three replicates. The doses, in g ha-1, were: diuron – 0, 1,250, and 2,550; indaziflam – 0, 50, and 100; metribuzin – 0, 480, and 960; and sulfentrazone – 0, 400, and 800. Cucumber (Cucumis sativus) was used as indicator species for diuron, indaziflam, and metribuzin, and sorghum (Sorghum bicolor) was used for sulfentrazone. The residual action in the soil of all herbicides evaluated caused injuries to the indicator plants, and the duration and intensity of which varied with the tested doses. The shortest residual action period was observed with the application of sulfentrazone at the lowest dose (400 g ha-1), and the longest with the application of indaziflam at the highest dose (100 g ha-1), 21 and 231 days after application, respectively.